Recent cannabis use among Veterans in the United States: Results from a national sample. (January 2018) - Davis, Alan K.; Lin, Lewei A.; Ilgen, Mark A.; Bohnert, Kipling M.
Abstract: Background: Compared to civilians, little is known about cannabis use among Veterans in the general United States (US) population. This study aimed to examine the prevalence and correlates of recent medical and non-medical cannabis use among this important US sub-population. Method: Data came from the 2014 National Survey on Drug Use and Health. Bivariate and multivariable analyses were conducted that were weighted to account for the complex survey design. Results: Approximately 9% of Veterans in the US reported past year cannabis use. Older, and female, Veterans had lower odds of past year cannabis use. Veterans who were unmarried, out of the work force, had greater functioning disability, nicotine dependence, heavy episodic alcohol use, alcohol use disorder, and drug use had greater odds of past year cannabis use. In states where medical cannabis was legal in 2014, approximately 41% of Veterans who used cannabis in the past year used medically . Those who used medically were older and less likely to engage in recent heavy episodic drinking or to meet criteria for alcohol abuse/dependence, compared to Veterans using non-medically. Conclusion: Compared to non-Veterans in the US general population, recent cannabis use was similar or slightly lower among Veterans. However, among those with past year use, the proportion of those using medically was more than double that of the general population. Because only non-medical cannabis use was associated with higher rates of heavy episodic alcohol use and alcohol use disorder, it may be important to address problematic alcohol consumption among this high-risk group. Highlights: 9% of US Veterans reported past year cannabis use. Heavy episodic alcohol use is related to non-medical cannabis use. Alcohol use disorder is also related to non-medical cannabis use. 41% of Veterans using cannabis reported that they used cannabis medically.